IT IS BETTER TO BUY AT THE OFFICIAL STORE OR PREMIUM STORE AT E-COMMERCE - Johan, Suwinto (Jurnal Ilmiah Ekonomi Bisnis, 2024)
E-commerce is a highly popular method of buying items right now. One of the many well-known e-commerce sites where many individuals are vying to create their own businesses is Tokopedia. Large corporations operate independently, but they also create their own official storefronts to entice customers to buy products directly from them without going through middlemen and benefiting from the Tokopedia guarantee. In order to draw clients and receive a guarantee from Tokopedia, retailers other than official stores and stores that are operated independently can upgrade to premium shops by paying a monthly charge. Potential customers take this into account because not all the things they desire are available in the official store. This study examines whether sales, establishment, operating hours, rating, and the number of couriers would affect consumers' decisions to make purchases from official stores and premium retailers.